PAKISTAN BALANCING ACT: NAVIGATING FOREIGN POLICY BETWEEN SAUDI ARABIA AND IRAN - Yasir Inam; Amir Saeed; Raifat Ullah Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
The research paper takes a deep dive into how Pakistan walks the tightrope of foreign policy with Saudi Arabia and Iran on either side. It’s all about the fine line that Pakistan has to tread, and this study digs into those real moments when Pakistan had to make some tough calls between the two. It looks at how Pakistan responds to sticky situations in the region, and the kind of diplomatic backflips it has to do. Plus, the paper doesn’t just stop there. It also looks at Pakistan’s take on big issues that the Saudi-Iran rivalry stirs up and what this tug-of-war means for Pakistan’s choices. The research doesn’t miss a beat—it covers everything from the smooth diplomatic moves to the sharp economic plays and the security tactics Pakistan uses. It’s kind of like getting a backstage pass to see how Pakistan keeps its balance when the regional scene gets shaky. By really getting into these examples, the study adds some serious depth to what we understand about Pakistan’s foreign policy dance moves and how it holds its own in the Middle East’s ever-changing theatre.